Retooling incentive mechanisms for effective smallholder tree growers' contributions to global landscape restoration. Issue 1 (2nd January 2023) - Kumeh, Eric Mensah; Kyereh, Boateng; Asante, Joseph; Ohene-Gyan, Godfred; Nassah, Valerie Fummey; Asare, Alexander; Bosu, Paul P.; Nketiah, Samuel Kwabena
ABSTRACT: Amid the global tree-planting rush to restore degraded landscapes, this study examined how service providers organise incentives for smallholder forest plantations in rural Ghana. Current incentives push farmers to plant trees without adequate mechanisms for ensuring they benefit over time. This enables timber merchants to exploit many tree growers, discouraging most farmers from participating in restoration activities. While some tree growers innovate, converting their plantations into a sustainable charcoal system, land tenure insecurity and poor access to finance remain barriers policymakers, governments, and development practitioners must overcome to reinforce smallholders' contributions and ability to benefit from landscape restoration perennially.